2001
DOI: 10.1046/j.1540-8167.2001.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Size Reduction as a Predictor of the Success of Radiofrequency Maze Procedure for Chronic Atrial Fibrillation in Patients Undergoing Concomitant Valvular Surgery

Abstract: Atrial size reduction appears to predict the success of sinus conversion with the RF maze procedure used in conjunction with valvular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 4 publications
3
68
0
6
Order By: Relevance
“…Instead, it revealed that there were only 2 significant factors associated with the successful maintenance of SR: increase in the MV area and decrease in the LA size by PTMV. These findings are consistent with those of a recent study 18 in which atrial size reduction, not AF duration or preoperative atrial size, was found to predict the success of conversion and maintenance of SR in rheumatic AF patients undergoing concomitant radiofrequency maze procedure and valvular surgery.…”
Section: Predictors Of Successful Maintenance Of Sr In Rheumatic Af Asupporting
confidence: 92%
See 1 more Smart Citation
“…Instead, it revealed that there were only 2 significant factors associated with the successful maintenance of SR: increase in the MV area and decrease in the LA size by PTMV. These findings are consistent with those of a recent study 18 in which atrial size reduction, not AF duration or preoperative atrial size, was found to predict the success of conversion and maintenance of SR in rheumatic AF patients undergoing concomitant radiofrequency maze procedure and valvular surgery.…”
Section: Predictors Of Successful Maintenance Of Sr In Rheumatic Af Asupporting
confidence: 92%
“…Catheter ablation is seldom performed in rheumatic AF patients, 23 but in those studies that have used it, the success rate was limited. 11,12 The intra-operative radiofrequency maze procedure 18 is an option only for patients undergoing concomitant open-heart surgery for MV replacement. Thus, the strategy we studied here represents a feasible alternative treatment option in select patients after PTMV and may be justified in patients subject to the possible risk of sideeffects from long-term amidarone use, because AF can be converted to SR and the risk of thromboembolism can be reduced.…”
Section: Study Limitationsmentioning
confidence: 99%
“…39 Factors that influence procedure success include larger left atrial size, longer duration of AF, and choice of lesion set in permanent AF. 40,41 The development of new techniques and operations for surgical treatment of AF has caused a change in cardiac surgical practice. At the Cleveland Clinic, our current policy is to perform ablation in almost all patients coming to the operating room with preexisting AF.…”
Section: New Approaches For Surgical Af Ablationmentioning
confidence: 99%
“…Atriyal fibrilasyon ve sol atriyal çap ile ilgili yapılan çalışmalarda; nonvalvuler AF'si olan hastalarda sol atriyal çap 47 mm ölçülmüştür 11 . Radyofrekans ablasyonla ilgili yapılan bazı araştırmalarda, sol atriyal büyüklüğün başarıyı etkilediği bildirilmesine rağmen, diğer araştırmacılar tarafından doğrulanmamıştır 12 . Çapı 5 cm'nin altında olan hastalarda sinüs ritmine dönüş, 5 cm' nin üzerinde olan hastalara göre yüksek bulunmuş ancak; hasta sayısı az olduğundan ististiksel olarak anlamlı bulunmamıştır.…”
Section: Discussionunclassified